Bolstering The Growth of Broiler Chicken with Bio-Stimulant as Supple-ment in Drinking Water - Oñal, Jr., Paulino A; Baylon, Jude G.; Lobaton, Jr., Eugene G.; Pelagio , Niña Marace C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The most popular domestic animals in poultry raising are birds, such as chickens, geese, turkeys, and ducks. This study aims to bolster the growth performance of broiler chicken by supplementing bio-stimulant in the drinking water. This was conducted last January 1 to February 7, 2024 at Bacolod City, Philippines. The total number of birds used for this study was 80 broiler chickens. The researchers gathered data on the broiler chicken's weight, average daily gain, and feed conversation ratio within 35 days. The researchers used a com-plete randomized design (CRD) with four treatments replicated four times. All the data gathered were statistically computed, and subject-ed to analysis of variance (ANOVA) in CRD using STAR 2.0.1. Results show that supplementing drinking water with 0.30% BSS mixtures had the heaviest weight of broiler chickens with 0.6984 kg, 1.3321 kg, and 1.7764 kg at weeks 3, 4, and 5, respectively. The same concentra-tion implied broiler chickens' highest average daily gain (ADG) weight with 0.0998 kg, 0.1903 kg, and 0.2538 kg at weeks 3, 4, and 5, respectively. Significant results were also shown by the same concen-tration with the lowest feed conversion ratio (FCR) at 1.47, 1.36, and 1.34 at weeks 3, 4, and 5, respectively. Based on the results of the study it recommends supplementing the drinking water of broiler chickens with BSS at a concentration of 0.30%.